2012
DOI: 10.1210/jc.2012-1527
|View full text |Cite
|
Sign up to set email alerts
|

Functional SNPs within the Intron 1 of the PROP1 Gene Contribute to Combined Growth Hormone Deficiency (CPHD)

Abstract: Variations with a functional significance conferring susceptibility to CPHD have been identified in the PROP1 gene, indicating a multifactorial origin of this disorder in sporadic cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Since defects in the regulatory regions of a gene can alter expression of the gene, variations in regulatory regions of pituitary transcription factors are likely to also cause isolated or combined pituitary hormone deficiencies. This is supported by the work of Godi et al [ 7 ], who found an association between two polymorphisms within and around a regulatory region in the intron 1 of PROP1 (rs73346254A and rs148607624 delTAG), and combined pituitary hormone deficiencies (CPHD). Co-presence of the alternative alleles of both SNPs was associated with reduced transcriptional activity as shown by a decreased luciferase activity.…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…Since defects in the regulatory regions of a gene can alter expression of the gene, variations in regulatory regions of pituitary transcription factors are likely to also cause isolated or combined pituitary hormone deficiencies. This is supported by the work of Godi et al [ 7 ], who found an association between two polymorphisms within and around a regulatory region in the intron 1 of PROP1 (rs73346254A and rs148607624 delTAG), and combined pituitary hormone deficiencies (CPHD). Co-presence of the alternative alleles of both SNPs was associated with reduced transcriptional activity as shown by a decreased luciferase activity.…”
Section: Introductionmentioning
confidence: 62%
“…We did not find any variants in the HESX1 promoter in either the (p)IGHD or CPHD patients. Four of the PROP1 promoter SNPs have been previously reported by Godi et al [ 7 ]. The genotype frequencies did not differ significantly from the frequencies found in healthy controls from the 1000 Genome Project (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding can be explained by the genetic heterogenity of the disease, by a multifactorial etiology determined by low penetrance genetic factors, or by phenocopies resulting from unknown acquired causes (34,36) .…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, ATBF1 not only activates expression of Pit1 gene though interacting with Pit1 enhancer ( Qi et al, 2008 ), but also potentially synergizes with PROP1 that can bind to the enhancer of Pit1 gene and regulate the expression levels of growth hormone, prolactin, and TSH-β ( Carvalho et al, 2006 ; Davis et al, 2010 ; Araujo et al, 2013 ). STAT3 , Pit1 , and PROP1 genes play an important role in embryo early development and cell differentiation ( Zhong et al, 1994 ; Schindler et al, 1995 ; Darnell, 1997 ; Heinrich et al, 1998 ; Shuai et al, 1999 ; Kamohara et al, 2000 ; Fang et al, 2012 ; Godi et al, 2012 ; Akcay et al, 2013 ; Pan et al, 2013 ; Navardauskaite et al, 2014 ), so ATBF1 gene was hypothesized to produce important effects on early development and cell differentiation, thus it would affect the grow traits in animals.…”
Section: Introductionmentioning
confidence: 99%